Centralized scheduling, decentralized scheduling or demand scheduling? How to more effectively allocate and recycle shared takeout lunch boxes - Bai, Yuntao; Liu, Di; Ma, Jili (PloS one, 2025)
Efficient scheduling of shared takeaway containers plays a significant role in the sharing economy system. An effective scheduling system ensures the maximization of container reuse, reducing resource waste and environmental pollution. To explore the applicability of different scheduling models for shared takeaway containers, this paper constructs differential game models for three modes: centralized scheduling, decentralized scheduling, and demand-based scheduling. The equilibrium outcomes are compared and analyzed. The research findings indicate that when the revenue from scheduling takeaway containers is low, decentralized scheduling can yield the maximum benefit for takeaway platforms; conversely, when the revenue is high, centralized scheduling offers the greatest benefit. For restaurant enterprises, when the revenue from scheduling is low, if the cost of scheduling is also low, demand-based scheduling can provide the maximum benefit; however, if the cost is high, decentralized scheduling is more advantageous; otherwise, centralized scheduling can maximize the benefits for restaurant enterprises.